Kesadaran Mengenai Digital Safety di Kalangan Guru Sekolah Dasar - Roy Ardiansyah; Syafni Nur Afifah; Hasan Mahfud (Universitas Sebelas Maret, 2021)
This study aims to examine elementary school teachers’ awareness of digital safety. The digital safety in this study are comprised of four competencies as indicator, such as: (1) protecting device; (2) protecting personal data and privacy; (3) protecting health and well-being; (4) protecting environment. This study use triangulation design of mix-method approach, with both quantitative and qualitative data collection. This study is conducted on SD Negeri Mangkubumen Lor No. 15, a public school in Laweyan, Surakarta. The subjects of this study are 20 teachers of SD Negeri Mangkubumen Lor No. 15. Quantitative and qualitative data collection both used to explore teacher’s knowledge, attitude and behavior toward digital safety through the use of questionnaire, semi structured interview and secondary data gatheting. The result of this study found that the teachers already have awareness about digital safety in all four indicators of digital safety. However, their guidance regarding student’s digital safety still limited only on protecting health and well-being indicator. The finding also implicate that there’s a need of continuous improvement and transformation regarding teachers’ digital literacy as to welding future digital risk as well as the need of parents’ collaboration.